Identyfikacja i pomiar ryzyka pogodowego w przedsiębiorstwie - Kupczyk, Józef (Identification and Measurement of Weather Risk in a Firm, 2005)
Earnings of many firms depend on weather conditions, for example observed temperature, precipitation, wind speed etc. In these situations it can be said that firms are exposed to weather risk. This paper presents a method for identification and measurement of this risk in a firm, especially the impact of weather conditions on the volume of sales is considered.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 200-209